Irregular amplitude variations and another abrupt period change in the δ Scuti star V 1162 Ori - Arentoft, T.; Sterken, C.; Knudsen, M. R.; Handler, G.; Niarchos, P.; Gazeas, K.; Manimanis, V.; Moalusi, M. B.; Vuthela, F. F.; van Cauteren, P. (2001)
We report that the intermediate amplitude delta Scuti star V 1162 Ori has changed its main pulsational period in the course of the year 2000. This new period change falls in a sequence of period changes observed during the last 5 years. While the average amplitude value of all our new data, 63 mmag, fits a cyclic amplitude variation suggested by Arentoft et al. (2001), splitting the data up in smaller subsets discloses significant deviations from regularity, with stretches of constant amplitude during short intervals of time. The new data show that the amplitude of one of the secondary frequencies, f2, has in 3 years dropped from more than 3 mmag to now about 1 mmag, and that the previously obtained f5 probably is a 1 d-1 alias of the real frequency. We present the newly acquired times of minimum and maximum light as support for subsequent observing campaigns. Based on observations obtained at the South African Astronomical Observatory (SAAO), Athens University Observatory, the Danish 1.5 m telescope at ESO, La Silla, Chile, and Beersel Hills Observatory.
Keywords: methods: data analysis; STARS: INDIVIDUAL: V 1162 ORIONIS; STARS: VARIABLES: DELTA SCUTI; techniques: photometric